IMPUTASI MENGGUNAKAN PENAKSIR REGRESI UNTUK MENAKSIR RATA-RATA POPULASI PADA SAMPLING GANDA - Bernad Fundika Marpaung; Rustam Efendi; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Estimators discussed in this paper are estimators that estimate a population mean with imputation method under double sampling design using regression estimators. Imputation methodsare used to estimate the missing data. This is a review of an article written by Thakur et. al [Journal of Reliability and Statistical Studies, 5(2): 21- 31]. There are three estimators that discussed and each of them is an unbiased estimator. The minimum variance of each estimator is compared in order to decide the most efficient estimator.